Ultrasonic assisted SiO2 nanoparticles strengthened Al/Cu plasma arc fusion brazing welding process - FAN Ding; ZHANG Huan; HUANG Jiankang; LI Yan; XIE Yuhang (Cailiao gongcheng)
The joining of aluminum/copper dissimilar metals is successfully achieved by ultrasonic-assisted nano-enhanced plasma arc fusion brazing， and a well-formed aluminum/copper lap joint is obtained. The effects of ultrasonic waves and SiO2 nanoparticles on the macroscopic and microscopic morphology， organizational structure， mechanical properties and conductive properties of lap joints are analyzed and studied by SEM， EDS， XRD， tensile test and conductivity test. The results show that the lap joint is obtained under the coupling action of ultrasonic waves and SiO2 nanoparticles， and the spreading and wetting effect of liquid aluminum on the copper surface is better， the front side of the weld is well formed， and the joint is mainly composed of intermetallic compound layer region and Al-Cu eutectic region. The thickness of the intermetallic compound layer is reduced obviously，and the mechanical properties of the joint is significantly improved. The relative conductivity of the aluminum/copper joint using SiO2 nanoparticles and ultrasonic waves is 153.527%IACS， exhibiting improved mechanical properties and electrical conductivity.